2016
DOI: 10.1007/s10571-016-0344-5
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Phenylbutyrate and Edaravone Abrogate Chronic Restraint Stress-Induced Behavioral Deficits: Implication of Oxido-Nitrosative, Endoplasmic Reticulum Stress Cascade, and Neuroinflammation

Abstract: Chronic stress exposure can produce deleterious effects on the hippocampus (HC) which eventually leads to cognitive impairment and depression. Endoplasmic reticulum (ER) stress has been reported as one of the major culprits in the development of stress-induced cognitive impairment and depression. We investigated the neuroprotective efficacy of sodium phenylbutyrate (SPB), an ER stress inhibitor, and edaravone, a free radical scavenger, against chronic restraint stress (CRS)-induced cognitive deficits and anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 67 publications
3
75
0
1
Order By: Relevance
“…For example, disturbance of brain hydrogen sulfide generation has been shown to promote the formation of depression-like behaviors via induction of ER stress [57]. In addition, sodium phenylbutyrate, a well-known inhibitor of ER stress, is reported to abrogate depression-like behaviors induced by chronic restraint stress via attenuation of neuroinflammation, oxido-nitrosative stress, and ER stress [22]. Our results regarding the improvement effects of TUDCA on mice depression-like behaviors further support the role of neuroinflammation, oxido-nitrosative stress, and ER stress in depression formation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, disturbance of brain hydrogen sulfide generation has been shown to promote the formation of depression-like behaviors via induction of ER stress [57]. In addition, sodium phenylbutyrate, a well-known inhibitor of ER stress, is reported to abrogate depression-like behaviors induced by chronic restraint stress via attenuation of neuroinflammation, oxido-nitrosative stress, and ER stress [22]. Our results regarding the improvement effects of TUDCA on mice depression-like behaviors further support the role of neuroinflammation, oxido-nitrosative stress, and ER stress in depression formation.…”
Section: Discussionmentioning
confidence: 99%
“…1. SPB was prepared freshly in saline everyday, and the selected doses of SPB and LPS were chosen based on the previous study performed in our laboratory [3,18]. On the seventh day, LPS (0.83 mg/kg) was administrated into mice 30 min after drug administration.…”
Section: Animalsmentioning
confidence: 99%
“…Sodium phenylbutyrate (SPB) is a low molecular weight fatty acid that is approved by FDA for the treatment of urea cycle disorders in human. Numerous studies revealed the ER stress inhibition capacity of SPB in different animal models [16][17][18][19]. SPB acts as a chemical chaperone that supports the posttranslational modification, folding of unfolded proteins, and thereby, reduces the protein-folding load of ER.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports using the MWM test, a test used to assess spatial learning and memory, have shown that aging reduces both spatial learning and memory (Eichenbaum et al, 2017; Jordan, 2020). In agreement with previous reports in adult mice (Jangra et al., 2017; Xu et al., 2015; Yao et al., 2014), our results suggest that the PBA improves the response of the old mice, in the MWM test, for both the learning and for the memory process. This cognitive improvement was not related to an increase in locomotor activity in a new environment.…”
Section: Discussionmentioning
confidence: 99%
“…How PBA increases the number of dendritic spines of the pyramidal neurons of the PFC, the CA1 subregion of the hippocampus and medium spiny neurons of the NAcc in old mice is not known at the present time. However, several reports have suggested that PBA has anti‐inflammatory and antioxidant properties (Jangra et al., 2017; Wang, Zhang, Jiang, & Zhang, 2018; Zeng et al., 2017). In addition, recent reports also suggest that PBA reduces endoplamasmic reticulum (ER) stress (for review see Khan, Komarya, & Jena, 2017).…”
Section: Discussionmentioning
confidence: 99%